Elements of coprosemiotics - Surace, Bruno (E|C, 2020)
Food and taste are spheres explored with vigor in recent years, in all the dimensions they involve, or almost. In fact, among these there is one that seems systemically eluded. It is the terminal but necessary dimension of food, one in which it naturally transforms itself from wonderful text in the dish into fecal mass. There is a taboo on poop, yet relegating it to the margins of the semiosphere, in the ravines of bad taste, in a symbolic repressed sewer. But it does not prevent it from being in effect a prolific producer of meaning. Poop is the linguistic universal founded on disgust, the place of a right symbology on the esthetic of the repugnant, which would seem refractory to any mise en langue. Yet it is always very semioticized. Through a path of texts, cinematographic and not only, in this essay we aim to reintroduce it into the semiotic debate, emphasizing the importance of a semiotics of disgust (complementary to that of taste), and laying the foundations for the development of a future general coprosemiotic.